2023
DOI: 10.1177/00220345221145555
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Organs-on-a-Chip in Dental, Oral, and Craniofacial Research

Abstract: The current development of microfluidics-based microphysiological systems (MPSs) will rapidly lead to a paradigm shift from traditional static 2-dimensional cell cultivation towards organized tissue culture within a dynamic cellular milieu. Especially organs-on-a-chip (OoCs) can very precisely re-create the mechanical and unique anatomical structures of the oral environment. This review provides an introduction to such technology, from commonly used chip materials and fabrication methods to the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…A deeper understanding of oral pathophysiology requires the development of 3D culture systems that can recapitulate the oral ECM structures, mechanics, and complex cell-cell and cell-matrix interactions that occur in vivo [51][52][53]. Recent studies have demonstrated the development of 3D microfluidic platforms that have been widely used in oral, dental, and craniofacial areas [54]. Specific efforts related to oral mucosa include the Gingival Crevice-On-Chip platform, which recapitulates host-oral microbiome interactions [55]; oral mucosa-on-a-chip, which has been applied to evaluate the responses of bacteria to dental materials [56]; and oral mucositis-on-a-chip, which investigates the role of chemo-and radiation treatments in oral tissue [56].…”
Section: Discussionmentioning
confidence: 99%
“…A deeper understanding of oral pathophysiology requires the development of 3D culture systems that can recapitulate the oral ECM structures, mechanics, and complex cell-cell and cell-matrix interactions that occur in vivo [51][52][53]. Recent studies have demonstrated the development of 3D microfluidic platforms that have been widely used in oral, dental, and craniofacial areas [54]. Specific efforts related to oral mucosa include the Gingival Crevice-On-Chip platform, which recapitulates host-oral microbiome interactions [55]; oral mucosa-on-a-chip, which has been applied to evaluate the responses of bacteria to dental materials [56]; and oral mucositis-on-a-chip, which investigates the role of chemo-and radiation treatments in oral tissue [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, such a configuration limits the ability to achieve the necessary air‐liquid interface culture required for the stratification and differentiation of keratinocytes, and the attainment of epithelial barrier function. [ 18 ] In contrast, the vertically stacked design combined with open access feature presented in this study, helps mimic the lumen of the oral cavity, and achieve the required air‐liquid interface for efficient differentiation of keratinocytes, and the formation of protective barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid control systems provide continuous nutrient supply, controlled delivery, and mechanical stimulation through active flow, resulting in a superior representation of the in vivo microenvironment. [16][17][18] Further, miniaturization helps to minimize sample size and reagent volumes needed for the assays. [19] Recent advancements in oral and dental barrier tissue emulation using microfluidic systems are gaining significant traction with platforms such as oral mucosa-on-chip, [20][21][22][23] gingival creviceon-chip, [24] gingival epithelial-capillary interface-on-chip [25] and tooth-on-chip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising novel fabrication techniques include 3D printing, [98,99] nanofabrication, [100,101] and microfluidics-based methods. [102,103] In summary, micropillars hold great promise in the field of stem cell research and tissue engineering. While the innovative techniques involving PDMS micropillar arrays and microfluidic chips have found success in other areas of regenerative medicine, their direct application to bone regeneration may necessitate further customization and exploration to effectively address the complex demands of bone tissue engineering.…”
Section: Conclusion and Prospective: Advancing Micropillar Technology...mentioning
confidence: 99%